Effect of Processing Methods on Some Antinutritional Factors in Legume Seeds for Poultry Feeding - Akande, K.E.; Fabiyi, E.F. (International Journal of Poultry Science, 2010)
Removal of undesirable components is essential to improve the nutritional quality of legumes and effectively utilize their full potential as poultry feed ingredient. It is widely accepted that simple and inexpensive processing techniques are effective methods of achieving desirable changes in the composition of seeds. Different authors have reported that soaking, cooking, toasting, autoclaving, microwave cooking, pressure cooking, extrusion cooking, germination and chemical treatment improve the quality of legumes because of the removal or inactivation of some anti-nutritional factors. In many instances, usage of only one method may not effect the desired removal of anti-nutritional substances and a combination of two or more methods may be required.